Diagnosis dan Tatalaksana Antraks - Susanto, Wenly (Cermin Dunia Kedokteran, 2023)
Anthrax is a zoonotic disease caused by the bacterium Bacillus anthracis. The source of anthrax transmission to humans is usually through contact with infected products or with infected ruminants such as goats, sheep, cattle, and buffalo. Anthrax is a priority for the Ministry of Health and the Ministry of Agriculture’s zoonotic control program. Addressing the significant public health impacts, economic losses, and bioterrorism threats requires a comprehensive interdisciplinary and community response. The knowledge and skills of medical personnel for earlier diagnosis and to provide appropriate treatment need to be increased by updating guidelines and cross-sector collaboration.